The Study of "Healthy Alley" and Home Care Program Policies to Develop Sustainable Health Innovation in Makassar, Indonesia - Haerana Haerana; Umar Congge; Suhardiman Syamsu; Eka Yulyana; Kisman Karinda (Journal of Governance and Public Policy, 2024)
This study describes the implementation of public service innovations (“Healthy Alley” and home care) in Makassar to disclose facts about the factors supporting innovations so that they can be sustainable in the future. Data were collected through a structured interview process with 14 informants and through observation by researchers. Secondary data were collected from national journal articles and annual report documents from the Department of Health, Makassar Regional Development, and Research Agency. Validity and reliability were addressed by triangulating data sources. Out of five innovation attributes, the “Healthy Alley” and home care innovations only met four standards. The research findings revealed that the home care innovation program has been well implemented compared to the "Healthy Alley" innovation program. This condition was due to the two different innovation programs in the handling system. The sustainability of public service innovation can be realized by taking into account several supporting indicators: 1. Commitment of Implementor; 2. User Participation; 3. Supported; 4. Network. Also, it is known that a public service innovation program with a good handling system will succeed in improving the quality of public service policies that affect innovation, but the budget will make things easier.